1999
DOI: 10.1152/jn.1999.82.4.1934
|View full text |Cite
|
Sign up to set email alerts
|

Pain Intensity Processing Within the Human Brain: A Bilateral, Distributed Mechanism

Abstract: Functional imaging studies of human subjects have identified a diverse assortment of brain areas that are engaged in the processing of pain. Although many of these brain areas are highly interconnected and are engaged in multiple processing roles, each area has been typically considered in isolation. Accordingly, little attention has been given to the global functional organization of brain mechanisms mediating pain processing. In the present investigation, we have combined positron emission tomography with ps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

81
548
9
6

Year Published

2000
2000
2013
2013

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 938 publications
(644 citation statements)
references
References 43 publications
81
548
9
6
Order By: Relevance
“…Interestingly, gabapentin also affected stimulus-induced deactivations, which suggests that the drug has substantial effects on attentional and arousal networks in the brain, in line with its sedative side effects. With respect to clinical pain, we recently confirmed the relationship between the subjective perception of pain intensity and the haemodynamic response, previously only described in healthy volunteers (53)(54)(55)(56)(57)(58). Out of several brain regions in which the magnitude of the FMRI signal encoded the perceived intensity of brush-evoked allodynic pain in neuropathic pain patients, the caudal anterior insula reflected the subjective allodynic pain ratings best (59) (Fig.…”
Section: Application Of Phfmri To Pain Researchsupporting
confidence: 81%
“…Interestingly, gabapentin also affected stimulus-induced deactivations, which suggests that the drug has substantial effects on attentional and arousal networks in the brain, in line with its sedative side effects. With respect to clinical pain, we recently confirmed the relationship between the subjective perception of pain intensity and the haemodynamic response, previously only described in healthy volunteers (53)(54)(55)(56)(57)(58). Out of several brain regions in which the magnitude of the FMRI signal encoded the perceived intensity of brush-evoked allodynic pain in neuropathic pain patients, the caudal anterior insula reflected the subjective allodynic pain ratings best (59) (Fig.…”
Section: Application Of Phfmri To Pain Researchsupporting
confidence: 81%
“…It is also suggested that these domains have a close relationship with the pain sensation system, as studies on patients with pain have recorded activity in these sites. A shift in the activated ECDs sites to the premotor cortex and supplementary motor area (SMA) following induced hyperalgesia in this study also indicates a relationship between the premotor cortex and pain sensation 13,14) .…”
Section: Discussionsupporting
confidence: 62%
“…In many respects, this approach is well founded although some reservations persist about the degree to which activations reflect functions that are common across both innocuous and noxious sensory processing. A significant increase in signal from a brain region during painful stimulation does not preclude the possibility that the region is involved in processes common to both pain and other sensory experiences, albeit in an intensity-dependent manner [Coghill et al, 1999]. Consequently, when considering the results of the ALE analysis, it is important to acknowledge that painrelated activity in this context does not translate to a network that is dedicated exclusively to pain perception per se.…”
Section: Discussionmentioning
confidence: 99%